2011
DOI: 10.1111/j.1365-2133.2011.10254.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of tumour necrosis factor (TNF)-α, interleukin (IL)-1β and IL-10 in hidradenitis suppurativa skin: a rationale for targeting TNF-α and IL-1β

Abstract: This study shows for the first time that IL-1β, TNF-α and IL-10 levels are elevated in HS skin. These data provide a rationale for therapies with biologics targeting cytokines such as TNF-α and IL-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
332
0
20

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(370 citation statements)
references
References 29 publications
18
332
0
20
Order By: Relevance
“…These include genetic predisposition, hormonal dysregulation and an aberrant immune response to commensal bacteria 7, 8, 9, 10. A number of exogenous influences have also been implicated in population‐based studies of HS, particularly smoking and obesity,11 although a causative relationship has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…These include genetic predisposition, hormonal dysregulation and an aberrant immune response to commensal bacteria 7, 8, 9, 10. A number of exogenous influences have also been implicated in population‐based studies of HS, particularly smoking and obesity,11 although a causative relationship has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that the IL-23/Th17 pathway is overexpressed in hidradenitis suppurativa (29), and this provides a rationale for the use of biologicals interfering with the Th17 pathway, like ustekinumab (anti-IL-12/IL-23) and anakinra (IL-1Ra) (see http://clinicaltrials.gov/ct2/show/ NCT01704534?termϭhidradenitisϩsuppurativa&rankϭ11 and http://clinicaltrials.gov/ct2/show/NCT01558375?termϭhidraden itisϩsuppurativa&rankϭ12). Given the known suppressive effect of IFN-␥ on the expansion of Th17 cells (28), the absence of IFN-␥ production in affected skin (30) and circulating lymphocytes as found here suggests a role of defective Th1 responses for the overproduction of IL-17A.…”
Section: Discussionmentioning
confidence: 99%
“…Több munkacsoport is megerősítette, hogy a léziós bőrben jelentősen emelkedett a TLR2, az IL-17A, az IL-1B, a TNFA és az IL-10 gének kifejeződése (4), melyek a jelen (TNF gátlók) és a jövő (IL-1 és IL-17 gátló) terápiás cél-pontjainak alapját adják (8). A sejtszintű karakterizálás során a gyulladásos infiltrátumban a neutrofilek és a hízó-sejtek mellett jelentős mennyiségben találtak IL-12-t és IL-23-at termelő makrofágokat a papilláris és a reticuláris dermisben, Il-1β-t termelő CD11c+ (dendritikus) sejteket, 130 (9).…”
Section: Gyulladásos Sejtek Hs-benunclassified
“…A sejtszintű karakterizálás során a gyulladásos infiltrátumban a neutrofilek és a hízó-sejtek mellett jelentős mennyiségben találtak IL-12-t és IL-23-at termelő makrofágokat a papilláris és a reticuláris dermisben, Il-1β-t termelő CD11c+ (dendritikus) sejteket, 130 (9). További megfigyelés a krónikus léziókban a CD20+ és a CD79a+ B sejtek, valamint a CD138+ plazmasejtek megjelenése, jelezve a patogenezis dinamizmusát (8). A TLR2 fokozott jelenléte a baktériumok és az azokból származó kismolekulák szerepét veti fel a betegség kialakulásá-ban/módosításában (3).…”
Section: Gyulladásos Sejtek Hs-benunclassified